FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI IBU DALAM MEMBAWA BALITA KE POSYANDU - Rahmaniza, - (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2018)
Since posyandu was build the in kelurahan Balai Ahad it is nothing posyandu able to reach up the national target in visiting posyandu. In the posyandu sayang ibu found were only 24% of children under five years old who come to posyandu meanwhile national target were 80%. The aim of this research was to know about factors that are related with mothers motivation in taking children under five years old to posyandu. The design of research is correlation that used cross sectional. A number of population were 30 people and sample 30 people. The samples this research are all mother who have mother of children under five years and old in Pincuran Tujuh and for taking of data finished by use questionnaires and testing statistic 0,05. The result of this research were 70% high education and 30% low education, 60% good knowledge about posyandu and 40% bad knowledge, there are 46,67% positive of posyandu and 53,3% have negative of posyandu, there are 60% to get motivation from family and there are 40% not able to get motivations from family. Respondents who are motivated in taking children under five year old to posyandu were 6 responden (20%) and 24 respondent (80%) no not motivated. Based on result of questionnaires are got that 5 respondent (22,73) have high education in taking children under five year old to posyandu, 6 respondent (33,33%) have good knowledge, are motivated in taking children under five year old to posyandu, 4 respondents (22,22%) have positive thinking, motivated in taking chidren under five year old to posyandu, 5 respondent (22,78%) get motivation from family and motivated in taking children under five year old to posyandu. Based on the statistical testing of statistic 0,05, got the meaningful relation with motherâs motivation in taking children under five year old to posyandu is variable education. From the result of this research, itâs necessary to provide intensively about health promotion to motivate mothers to take children under five year old to posyandu